Dilated Odontoma Arising in the Mandibular Third Molar Germ: Report of a Case of an Unusual Lesion in an Uncommon Site - Francesca Zara; Giacomo D’Angeli; Alessandro Corsi; Antonella Polimeni; Gian Luca Sfasciotti (Diagnostics, 2021)
Dilated odontoma is the most severe variant of dens invaginatus. It is extremely uncommon in the posterior mandible. It is thought to originate during the morpho-differentiation stage of dental development. However, its etiology and pathogenesis remain obscure. We report here the clinical and pathologic findings of an incidentally discovered dilated odontoma arising in the left third mandibular molar germ of an 11-year-old male and a review of the pertinent literature. As dilated odontoma is not established as an independent entity in the current WHO classification of odontogenic tumors and is the result of a well-established developmental anomaly of the tooth (that is, the invagination of the enamel organ into the dental papilla), it should be better identified as dilated dens invaginatus.